NCEA Level 2 Algebra Exam 2014

From last year’s Algebra exam: I couldn’t see how to rearrange \large{\boldsymbol{h=rx^2 -tx}} to make \large{\boldsymbol{x}} the subject.

You can find a copy of the exam question paper on the NZQA website here.

Question Two (c) (i): (abbreviated) Rearrange \boldsymbol{h=rx^2 -tx}, where \boldsymbol{r} and \boldsymbol{t} are constants, to make \boldsymbol{x} the subject.

The problem here is probably to do with the terminology they’ve used in asking the question. If you approach it as a typical ‘rearrange the equation’ question, and attempt to perform step-by-step rearrangement on it, you’re unlikely to get very far.

Instead, take a step back and look at the type of equation you’re dealing with. It’s a quadratic in \boldsymbol{x}. We have techniques for solving quadratics and, in doing so here, we will get a solution that looks like \boldsymbol{x}=\hdots, which is precisely the same thing as ‘making \boldsymbol{x} the subject’.

So let’s do it. We’ll start by rearranging the equation into the form we need for the Quadratic Formula:

\large{\boldsymbol{h = rx^2 -tx}} \\ \large{\boldsymbol{rx^2 -tx = h}} \\ \large{\boldsymbol{rx^2 -tx-h = 0}}

Now, the Quadratic Formula tells us that:

\large{\boldsymbol{\text{If } ax^2 +bx+c = 0\text{,}}}

\Large{\boldsymbol{\text{then }x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}}}

In our case we have \boldsymbol{a=r, b=-t, c=-h}. So let’s plug ‘em in and see what we get:

\Large{\boldsymbol{x=\frac{-(-t)\pm\sqrt{(-t)^2-4(r)(-h)}}{2(r)}}} \\ \Large{\boldsymbol{x=\frac{t\pm\sqrt{t^2+4rh}}{2r}}}

and we’re done.

Question/Comment

Your email address will not be published.

You may use these HTML tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <strike> <strong>